Counselling on Stunting in Children and How to Prevent it in Bengkok Village, Mahendra-Cibaliung, Pandeglang Regency - Ewing Yuvisa Ibrani; Yenny Dwi Handayani (MOVE: Journal of Community Service and Engagement, 2022)
The main purpose of this counseling is to provide clear information to mothers in Bengkok Village regarding what stunting is and how to prevent stunting in toddlers. Stunting disease is a physical growth disorder of toddlers characterized by a decrease in growth speed and impacts nutritional imbalances. Stunting illness can usually be seen from the condition of the toddler's height which is less when compared to his friends his age.Lack of nutritional intake in children is a picture of stunted toddlers. Socio-economic factors influence the high prevalence of stunting, including parents' economic status, family food security, parental education and knowledge, number of family members, sanitation, and environmental hygiene. Counseling on stunting and how to prevent it was carried out in Bengkok Village, Pandeglang in August 2022.